Intraobserver reliability of posturography in patients with vestibular neuritis - Schwesig, René; Fischer, David; Becker, Stephan; Lauenroth, Andreas (Somatosensory & motor research, 2014)
Posturography, reliability, vestibular neuritis
Online: 16 Aug 2013
Gesehen am 21.09.2020